Zaboravljeni akademik iz Argentine - Dončević, Ivona (Array, 2008)
The Quality Testing Station at La Consulti is named after Argentinean Academician Josip Crnka, an institution he founded and where this Croatian son earned a level of fame earned by few researchers within their own lifetime. He published over 60 research papers in Spanish and English, for which he received numerous international recognitions. Making innovations for the most part in the field of plant physiology, seed production and the improvement of various kinds of vegetables, he represented his new homeland of Argentina at numerous international symposiums. Argentina has honoured him with the title of Academician, while top academic circles in his country of origin continue to ignore him as a political emigrant.